SOSIALISASI DAN MANFAAT EKOENZIM DI AREA PETERNAKAN, PERTANIAN DAN PERIKANAN DI DESA CILINGGA KECAMATAN DARANGDAN KABUPATEN PURWAKARTA - Surtikanti, Hertien Koosbandiah; Hernawati, Hernawati; Surakusumah, Wahyu; Dewina, Utari; Kurniawan, Try (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, 2024)
Ecoenzymes are fermentation products from organic waste in the form of vegetables or fruit. Many people produce organic waste in households every day, including residents in Cilingga village, Purwakarta Regency. The aim of this community service activity (PkM) is to provide education in waste/waste management as additional information. Apart from that, it also provides knowledge and awareness of community groups in making ecoenzymes as a multi-functional product, which can overcome the problem of waste or organic waste, especially in households. The service method used is Participation Action Research (PAR) through certain stages. This PkM activity is carried out in several stages, namely discussion, socialization of activities and providing education through lectures and discussions, direct practice and filling out questionnaires. The results of this training in making ecoenzymes can help the community in maintaining environmental cleanliness, managing organic waste, both agricultural and livestock waste, as well as household waste. With this training, villagers can utilize their own organic waste into ecoenzymes. Apart from reducing organic waste entering the environment, this training can also create additional sources of income and increase awareness of the importance of maintaining environmental sustainability.